Coverage of extreme weather events and natural hazards in Pacific Island Countries: The need for media capacity-building - Shailendra Singh (Asia Pacific Network, 2018)
There would be little disagreement over the media’s crucial role in reporting extreme weather events and natural hazards, which have become more commonplace in Pacific Island Countries (PICs). However, for various reasons explored in this article, the media have generally failed to satisfactorily cover the unfolding of natural hazards and disasters. Using Fiji as an example, this article discusses media coverage of various cyclones, and the gaps in the reporting. The article argues that more training and capacity building for media personnel should be undertaken to ensure that people are well informed and prepared as they face the brunt of more frequent and intense extreme weather events.